Be 'estar' + participle in Spanish language: delimiting preiphrastic and attributive structures - Ortiz, Rosa María; Irigoyen, Karen (Lenguas Modernas, 2018)
The aim of this paper is to define the features of the periphrasis be ‘estar’ + participle, versus the same verb be ‘estar’ + participle, in not periphrastic but attributive structures, in current Spanish language. From a literary corpus of different genres, the analysis of the constructions includes both syntactic and semantic factors to discriminate the properties of the periphrasis from those of the attributive structure; and it also compares the structures be ‘estar’ + participle and be ‘ser’ + participle, a highly grammaticalized periphrasis, in order to prove that they have similar syntactic behavior, and therefore they are members of the same paradigm.